PERANCANGAN TRAFFIC LIGHT MENGGUNAKAN MODUL FIELD PROGRAMMABLE GATE ARRAY XILINX NEXYS 3 - Damayanti, Fatma Pandu (Universitas Diponegoro, 2018)
Traffic light is used to set transferring of the vehicle at the road junction to avoid congestion. Traffic light in Indonesia has fixed time without regard to congestion. This Final Assignment, advanced traffic light with limit switch sensor. The limit switch sensors were installed at each strip to detect heavy vehicles queue. The limit switch will be processed on FPGA Xilinx Nexys 3. Traffic light generates output, there are seven segments and LED used 1 Hz frequency. Seven segments used 4 digits to indicate lane North, South, East and West. Each digit on seven segments shown the turnover used 200 Hz frequency. Limit switch affect outputs on the length of time Green LED lights up. If the value of the limit switch = 1, the Green LED on certain lanes lights up for 7 seconds. If the value of the limit switch = 0, the Green LED on certain lanes light up for 5 seconds. The results on the Final Assignment is take two seconds of extra time for Green LED lights up if the value of the limit switch = 1. The value of the limit switches only take effect when the Green LED is lit for each lane.